Assessment of Reproductive Performances and Sex Ratio of Newborn in Cross Breed Dairy Cattle of Hawassa City, Ethiopia - Hailu, Tewabe; Duguma, Ararsa (Journal of Veterinary Healthcare, 2023)
Reproductive performance is an essential trait of cows in dairy cattle. The effect of different factors on reproductive performances and sex ratio difference in dairy cattle were not well documented in Ethiopia. In this research, cross-sectional study was conducted from December 2021 to June 2022 in Hawassa city to assess reproductive performances and effect of breeding methods on sex ratio difference of newborn. Questionnaires and observational study were used to collect data. In this study, the mean+SE of age at first service was 17.53+0.035 with difference of relatively one month from onset of puberty. The mean number of services per conception was higher in animals breed naturally (1.87+0.056) as compared to AI (1.69+0.049). Higher conception rate of 74.26% was obtained in age group of <4years as compared to old age >6years at rate of 4.11% with statistically significant difference (P<0.05). Animals with medium level of milk production (15-20L/day) more conceived to first service 43.14% than higher milk production group (20-25L/day) with 35.59%. The presence of reproductive problems significantly affect conception rate to first service with higher conception rate of 54.47% in negative animals and 22.41% in animals with reproductive problems. Conception rate was increased with increasing number of services in both breeding types. Sex of newborn was not significantly affected by breeding methods used and difference in the study area. Generally this research found that reproductive performances and use of AI in the study area were satisfactory even though age, level of milk production and presence of reproductive health problems had significant impacts on performances. In order to sustain and improve reproductive performances age, reproductive health problems and breeding management should be considered. Therefore, reproductive health management and application of AI for genetic improvement should be well practiced to improve dairy cattle reproductive performances.
Keywords: Artificial Insemination; Dairy farm; Hawassa city; Reproductive performance; Sex ratio